Comparison of the seed nutritional composition between conventional varieties and transgenic soybean overexpressing Physaria FAD3‐1 - Kim, Eun‐Ha (John Wiley & Sons, Ltd., 2021)

(untitled) (J Sci Food Agric)
BACKGROUND: PfFAD3 transgenic soybean expressing omega‐3 fatty acid desaturase 3 of Physaria produces increased level of α‐linolenic acid in seed. Composition data of non‐transgenic conventional varieties is important in the safety assessment of the genetically‐modified (GM) crops in the context of the natural variation. RESULTS: The natural variation was characterized in seed composition of 13 Korean soybean varieties grown in three locations in South Korea for 2 years. Univariate analysis of combined data showed significant differences by variety and cultivation environment for proximates, minerals, anti‐nutrients, and fatty acids. Percent variability analysis demonstrated that genotype, environment and the interaction of environment with genotype contributed to soybean seed compositions. Principal component analysis and orthogonal projections to latent structure discriminant analysis indicated that significant variance in compositions was attributable to location and cultivation year. The composition of three PfFAD3 soybean lines for proximates, minerals, anti‐nutrients, and fatty acids was compared to a non‐transgenic commercial comparator (Kwangankong, KA), and three non‐transgenic commercial varieties grown at two sites in South Korea. Only linoleic and linolenic acids significantly differed in PfFAD3‐1 lines compared to KA, which were expected changes by the introduction of the PfFAD3‐1 trait in KA. CONCLUSION: Genotype, environment, and the interaction of environment with genotype contributed to compositional variability in soybean. PfFAD3‐1 soybean is equivalent to the conventional varieties with respect to these components. © 2020 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.